THE IMPORTANCE OF EMOTION IN ENGLISH - Lyu Jiaying (Western European Studies, 2024)
The concept of emotion plays a crucial role in linguistics, influencing various aspects of language structure, communication, and meaning. Here are some key points on how the concept of emotion intersects with linguistics: 1. Semantic Analysis: Emotions are central to the meaning of words and phrases. Linguists study the semantics of emotion-related terms and how they are used to convey specific emotional states. For example, words like "happy," "sad," "angry," etc., carry emotional connotations that shape their meaning.
Keywords: connotations; emotional; Linguists; happy